CONSERVATIVE APPROACH TO DEEP CARIES LESIONS MANAGEMENT IN CHILDREN - N.V. Yanko (Український стоматологічний альманах, 2019)
The aim of the study was to systematize effective deep caries management methods in children in order to determine the indications for their use. The author used Google search engine to find articles and scientific publications published between 2006 and 2019.